Research gaps in the neurodevelopmental assessment of children with complex congenital heart defects: a scoping review - Hofer, Johannes; Blum, Marina; Wiltsche, Regina; Deluggi, Nikoletta; Holzinger, Daniel; Fellinger, Johannes; Tulzer, Gerald; Blum, Gina; Oberhuber, Raphael (Frontiers in Pediatrics, 2024)
Background: Children with congenital heart defects (CHD) are at risk for a range of developmental disabilities that challenge cognition, executive functioning, self-regulation, communication, social-emotional functioning, and motor skills. Ongoing developmental surveillance is therefore key to maximizing neurodevelopmental outcome opportunities. It is crucial that the measures used cover the spectrum of neurodevelopmental domains relevant to capturing possible predictors and malleable factors of child development.Objectives: This work aimed to synthesize the literature on neurodevelopmental measures and the corresponding developmental domains assessed in children aged 1-8 years with complex CHD. Methods: PubMed was searched for terms relating to psycho-social, cognitive and linguisticcommunicative outcomes in children with CHD. 1,380 papers with a focus on complex CHD that reported neurodevelopmental assessments were identified; ultimately, data from 78 articles that used standardized neurodevelopmental assessment tools were extracted. Results: Thirty-nine (50%) of these excluded children with syndromes, and 9 (12%) excluded children with disorders of intellectual development. 10% of the studies were longitudinal. The neurodevelopmental domains addressed by the methods used were: 53% cognition, 16% psychosocial functioning, 18% language/communication/speech production, and 13% motor development-associated constructs. Conclusions: Data on social communication, expressive and receptive language, speech motor, and motor function are underrepresented. There is a lack of research into everyday use of language and into measures assessing language and communication early in life. Overall, longitudinal studies are required that include communication measures and their interrelations with other developmental domains.